Effect of vibration on heat transfer and pressure drop in a heat exchanger with turbulator - Mohammed, Azeez Majeed; Kapan, Sinan; Şen, Murat; Çelik, Nevin (My University, 2021)
In the present study effects of forced mechanical vibration on a concentric pipe heat exchanger with turbulator inside it, is experimentally analyzed. Three different zigzag shaped turbulators are used in the concentric type heat exchanger. Air is preferred as the working fluid with inlet Reynolds numbers varying from ~10,000 to ~55,000. The effect of vibration on heat transfer and pressure drop is tested by using a mechanical vibration test unit. The variable parameters of the vibration phenomena are considered to be acceleration (amplitude) (a =100, 300 and 600 m/s2), frequency (F =100, 300 and 600 Hz) and signal type (sine, chirp and random noise). Effects of the vibration on heat transfer are shown by means of thermal performance factor (?) which includes Nusselt number and friction factor in the same formula. As a result, it is observed that, regardless of the variation of the frequency, acceleration or signal type, applying vibration to the turbulator increases the heat transfer and pressure loss simultaneously. For example, the highest heat transfer enhancement is found as 116% whilst the maximum enhancement per-centage of the friction factor is about 95%. It is also found that increasing frequency has more effect than increasing acceleration or changing signal types.
Türbülatörlü bir ısı eşanjöründe titreşimin ısı transferi ve basınç düşüşüne etkisi
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Makale - Yabancı Dilde Makale
Keywords: Vibration; Heat transfer; Turbulators; Heat exchangers